Assertive Communication Skills Group Intervention for Adolescents with Social Anxiety - Hayya, Rahmah Nurul; Savitri, Luh Surini Yulia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
National surveys show that most adolescents experience anxiety problems and anxiety disorders, but only a few seek professional help. Anxiety, especially social anxiety, can be detrimental to adolescents because of its impact on social success. If it persists, social anxiety can develop into social anxiety disorder as an adult. Thus, it is necessary to intervene in adolescents with high social anxiety. Adolescents with social anxiety often experience social situations that they cannot cope with due to a lack of social skills, especially assertive communication skills. This study aimed to see whether assertive communication skill interventions carried out in groups can improve adolescents' assertive communication skills and reduce social anxiety levels. Group interventions conducted in schools provide easy access for youth and efficiency in terms of time and cost. Group interventions also allow adolescents to voice their experiences, finding similarities and connect with others. The study participants were six teenagers aged 13-15 years with high levels of social anxiety. This study consisted of a pre-test, four intervention sessions, post-test, and follow-up. The Social Anxiety Scale for Adolescents (SAS-A) and Skala Tingkah Laku Asertif (STLA) were used to describe the participants' social anxiety and assertiveness before, after, and two weeks after the intervention. The results showed an increase in the STLA score and a decrease in the SAS-A score in most participants quantitatively and an increase in assertive communication skills and a decrease in social anxiety qualitatively in all participants. The implication of this study is that assertive communication skills intervention programs carried out in groups are beneficial in increasing assertive communication skills and reducing the level of social anxiety in adolescents, these results can be used as reference material in the intervention of adolescents with social anxiety. Survei nasional menunjukkan bahwa mayoritas remaja mengalami masalah kecemasan dan gangguan kecemasan, namun sedikit yang mencari bantuan profesional. Kecemasan, terutama kecemasan sosial, bisa merugikan karena dampaknya terhadap kesuksesan sosial. Jika berlanjut, kecemasan sosial dapat berkembang menjadi gangguan kecemasan sosial saat dewasa. Dengan demikian, perlu dilakukan intervensi pada remaja dengan kecemasan sosial tinggi. Remaja dengan kecemasan sosial seringkali mengalami situasi sosial yang tidak bisa mereka atasi karena kurangnya keterampilan sosial, terutama keterampilan komunikasi asertif. Penelitian ini bertujuan untuk melihat apakah intervensi keterampilan komunikasi asertif yang dilakukan secara berkelompok dapat meningkatkan keterampilan komunikasi asertif dan menurunkan tingkat kecemasan sosial remaja. Intervensi kelompok yang diadakan di sekolah memberikan kemudahan akses bagi remaja dan efisiensi dari segi waktu serta biaya. Intervensi kelompok juga memungkinkan remaja menyuarakan pengalaman, menemukan kesamaan, dan berkoneksi dengan orang lain. Partisipan penelitian merupakan enam remaja berusia 13-15 tahun dengan tingkat kecemasan sosial tinggi. Penelitian ini terdiri dari pre-test, empat sesi intervensi, post-test, dan follow-up. Social Anxiety Scale for Adolescent (SAS-A) dan Skala Tingkah Laku Asertif (STLA) digunakan untuk mengetahui gambaran kecemasan sosial dan asertivitas partisipan sebelum, sesudah, dan dua minggu sesudah intervensi. Hasilnya, terdapat peningkatan skor STLA dan penurunan skor SAS-A pada mayoritas partisipan secara kuantitatif dan peningkatan keterampilan komunikasi asertif serta penurunan kecemasan sosial secara kualitatif pada seluruh partisipan. Implikasi dari penelitian ini adalah bahwa program intervensi keterampilan komunikasi asertif yang dilakukan secara berkelompok bermanfaat dalam meningkatkan keterampilan komunikasi asertif dan menurunkan tingkat kecemasan sosial pada remaja sehingga dapat menjadi bahan rujukan dalam intervensi remaja dengan kecemasan sosial.